Practical applications of GPS and GIS in civil engineering and surveying half day meeting, Thursday 9 November 1995 at 2 pm (Thomas Telford, 1995)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a half-day meeting with ICES and RICS held on 9 November 1995.